Implementasi Project-Based Learning berbantuan Simurelay pada Mata Pelajaran Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Fival Pratama; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2026)
This study aimed to investigate the impact of implementing Project-Based Learning (PjBL) assisted by Simurelay on student learning outcomes in the Electrical Motor Installation course at SMK Negeri 1 Sumatera Barat. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 30 students from class XI TITL. Data were collected through pretest and posttest assessments, as well as practical skill evaluations. The results indicated a moderate improvement in learning outcomes, with a normalized gain score of 0.4. Additionally, 78% of students achieved the learning mastery criteria (KKTP) after the intervention, while 22% did not meet the standards. The practical skills assessment revealed that most students performed well, with 18 students categorized as "good" and 4 as "sufficient." The findings suggest that PjBL supported by Simurelay effectively enhances both cognitive and psychomotor skills in vocational education. This study contributes to the development of innovative teaching methods in technical subjects, emphasizing the integration of technology to improve student engagement and achievement.